2012
DOI: 10.1074/jbc.m112.387795
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronan and Layilin Mediate Loss of Airway Epithelial Barrier Function Induced by Cigarette Smoke by Decreasing E-cadherin

Abstract: Background: Cigarette smoke (CigS) induces hyaluronan fragmentation and increases epithelial permeability. Results: CigS and HA fragments decrease E-cadherin expression that is prevented by knocking down layilin. Conclusion: HA fragments bind to layilin and signal through RhoA/ROCK to inhibit E-cadherin. Significance: Airway epithelium is our first line of defense against inhaled insults. HA fragments released by CigS disrupt this barrier.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
72
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(76 citation statements)
references
References 79 publications
3
72
0
Order By: Relevance
“…Inhibition of Rho kinase reduced MLC phosphorylation, a target of the Rho/ROCK pathway, thus producing airway relaxation [51]. Cigarette smoke caused AJC disruption and increased epithelial permeability via triggering the RhoA/ROCK signaling pathway in bronchial epithelial cells [39]. In agreement with these findings, our study also found both HDM increased RhoA activity at 6 h and promoted MLC phosphorylation beginning 6 h, which remained elevated for many hours.…”
Section: Discussionsupporting
confidence: 84%
“…Inhibition of Rho kinase reduced MLC phosphorylation, a target of the Rho/ROCK pathway, thus producing airway relaxation [51]. Cigarette smoke caused AJC disruption and increased epithelial permeability via triggering the RhoA/ROCK signaling pathway in bronchial epithelial cells [39]. In agreement with these findings, our study also found both HDM increased RhoA activity at 6 h and promoted MLC phosphorylation beginning 6 h, which remained elevated for many hours.…”
Section: Discussionsupporting
confidence: 84%
“…In addition to the classic tight‐junction proteins claudins, occludins, and zonula occludens (ZOs), the adherens junction protein E‐cadherin also plays a pivotal role in tight‐junction development and maintenance. The absence or downregulation of E‐cadherin leads to the improper formation of tight junctions, resulting in permeability increase and dysfunction of epithelium barriers . Downregulation of E‐cadherin in BPH specimens was observed by our group and others .…”
Section: Introductionsupporting
confidence: 56%
“…Options include direct secretion from the airway epithelium, airway smooth muscle cells, goblet cells, mucus glands, or a combination of these. Among these options, the direct secretion from the airway epithelium and airways smooth muscle cells are the most likely, and several studies have demonstrated the ability of the epithelium and airways smooth muscle cells to secrete HA in vitro (3,37,38). The relatively negative staining of HA in goblet cell and mucous gland cell populations indicates that these cells are less likely to be involved in the secretion of HA into the airway lumen.…”
Section: Discussionmentioning
confidence: 99%